A Novel Resource Allocation Algorithm for OFDMA System with Proportional Fairness - Yaohui Wu; Youming Li; Pengfei Shao (Dianxin kexue)
Existing algorithms couldn't balance system capacity and high fairness well,so a multi-user rate adaptive allocation algorithm was proposed to maximize the capacity of OFDMA system under proportional fairness.Improved maximize the minimum（max-min）user rate model was proposed,the current user was allocated the highest efficiency subcarrier according to the channel efficiency control parameter.If some allocated subcarrier's channel gain was lower than the threshold value,which would be reallocated to another user whose channel gain was highest.Power allocation model was converted into expression of water-filling line; every user's power allocation was resolved according to the resolved water-filling line.Simulation results and analysis show that the proposed scheme can achieve higher capacity and perfect fairness in a variety of SNR cases,while requiring slightly less computation.